Synthesis of Polycarboxylate Rhodium(II) Metal–Organic Polyhedra (MOPs) and their use as Building Blocks for Highly Connected Metal–Organic Frameworks (MOFs). Issue 11 (29th January 2021) - Grancha, Thais; Carné‐Sánchez, Arnau; Zarekarizi, Farnoosh; Hernández‐López, Laura; Albalad, Jorge; Khobotov, Akim; Guillerm, Vincent; Morsali, Ali; Juanhuix, Judith; Gándara, Felipe; Imaz, Inhar; Maspoch, Daniel
Abstract: Use of preformed metal‐organic polyhedra (MOPs) as supermolecular building blocks (SBBs) for the synthesis of metal‐organic frameworks (MOFs) remains underexplored due to lack of robust functionalized MOPs. Herein we report the use of polycarboxylate cuboctahedral Rh II ‐MOPs for constructing highly‐connected MOFs. Cuboctahedral MOPs were functionalized with carboxylic acid groups on their 12 vertices or 24 edges through coordinative or covalent post‐synthetic routes, respectively. We then used each isolated polycarboxylate Rh II ‐MOP as 12‐c cuboctahedral or 24‐c rhombicuboctahedral SBBs that, upon linkage with metallic secondary building units (SBUs), afford bimetallic highly‐connected MOFs. The assembly of a pre‐synthesized 12‐c SBB with a 4‐c paddle‐wheel SBU, and a 24‐c SBB with a 3‐c triangular Cu II SBU gave rise to bimetallic MOFs having ftw (4, 12)‐c or rht (3, 24)‐c topologies, respectively. Abstract : Two different post‐synthetic routes have been followed to functionalize pre‐synthesized Rh II ‐based cuboctahedral metal–organic polyhedra (MOPs) with carboxylic acid groups, either on their 12 metal sites (vertices) or on their 24 linkers (edges). Such isolated MOPs serve as highly connected (12‐c and 24‐c) supermolecular building blocks, for the formation of two new bimetallic RhCu‐MOF structures.